Edukasi Kesehatan tentang Pengobatan Tradisional Hipertensi dengan Rebusan Daun Pandan pada Lansia di Puskesmas Air Besar - Windarti Rumaolat; Idham Soamole; Fathmy F. Soulissa (Jurnal Pelayanan Masyarakat, 2024)
Hypertension is the leading cause of premature death worldwide. To reduce the risk of hypertension, what needs to be done is hypertension treatment as an effort to control hypertension, one of which is non-pharmacological treatment, usually carried out by implementing the use of pandan wangi plants. Pandan wangi is a plant whose leaves are often used as a food additive. The purpose of implementing Community Service activities in Lorong Putri is to increase public awareness, especially the elderly, about Hypertension and the treatment of Hypertension with traditional medicine. Using the method of providing education and question and answer discussions related to dangerous conditions and efforts to prevent hypertension, participants in this activity were carried out on October 7, 2024 at Lorong Putri, Air Besar Health Center Work Area. totaling 20 people. During the Education Process, participants listened carefully and provided good feedback, in the form of benefits and how to consume boiled pandan leaf water, and whether it can be boiled together with drinking water at home, and all questions from participants can be answered well. With questions and answers from participants, participants can better understand hypertension and how to treat it with traditional medicine.